Fundamentals of Robotic Mechanical Systems Theory, Methods, and Algorithms - Angeles, Jorge; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
The 4th edition includes updated and additional examples and exercises on the core fundamental concepts of mechanics, robots, and kinematics of serial robots. New images of CAD models and physical robots help to motivate concepts being introduced. Each chapter of the book can be read independetly of others as it addresses a seperate issue in robotics.
An Overview of Robotic Mechanical Systems -- Mathematical Background -- Fundamentals of Rigid-Body Mechanics -- Geometry of Decoupled Serial Robots -- Kinetostatics of Serial Robots -- Trajectory Planning: Pick-and-Place Operations -- Dynamics of Serial Robotic Manipulators -- Special Topics in Rigid-Body Kinematics -- Geometry of General Serial Robots -- Kinematics of Alternative Robotic Mechanical Systems -- Trajectory Planning: Continuous-Path Operations -- Dynamics of Complete Robotic Mechanical Systems -- Kinematics of Rotations: A Summary -- Numerical Equation-Solving.
Keywords: Engineering; Mechanical engineering; Engineering; Mechanical Engineering; Robotics and Automation